Isolated annuloplasty in elderly patients with secondary mitral valve regurgitation: short- and long-term outcomes with a less invasive approach - Oezpeker, Ulvi Cenk; Hoefer, Daniel; Barbieri, Fabian; Gollmann-Tepekoeylue, Can; Johannes, Holfeld; Clemens, Engler; Suat, Ersahin; Adel, Sakic; Sasa, Rajsic; Mueller, Ludwig; Grimm, Michael; Bonaros, Nikolaos (Frontiers in Cardiovascular Medicine, 2023)
Background Long-term outcomes of elderly and frail patients with secondary mitral valve regurgitation (MR) are inconclusive. Especially in patients with co-morbidities such as atherosclerosis who are suffering from heart failure, optimal medical therapy (OMT) is the preferred therapy relative to surgical or percutaneous interventions. It remains challenging to identify the most successful therapy to improve symptoms and increase life expectancy. To reduce surgical trauma for these patients, minimally invasive mitral valve surgery (MIMVS) was developed; this has shown promising medium-term results, but there is still a lack of evidence regarding long-term results. The aim of this investigation was to describe the long-term outcomes of less invasive mitral valve surgery (MVS) in elderly patients. Methods In this longitudinal retrospective analysis, 67 patients (aged ≥70 years) with secondary MR who underwent MV repair ± tricuspid valve repair (TVR) were identified. MVS was performed via minithoracotomy (MT) in most cases (n = 54); in patients with contraindications for MIMVS, partial upper sternotomy (PS) was the preferred route for surgical access (n = 13). The appropriate access route was chosen according to the patient's clinical condition and comorbidities. We analyzed reoperation-free long-term survival, combined operative success (lack of residual MR, conversion to MV replacement, or larger thoracic incisions), and perioperative safety (at 30 days: mortality, re-thoracotomy, ECMO, pacemaker implantation, dialysis, longer ventilation, stroke, myocardial infarction). In a subgroup analysis, we compared long-term survival in MVS patients with and without TVR. Results The median age of patients (62.7% female) was 74 years (interquartile range: 72–76 years), with a median EuroSCORE2 of 2.8% (1.5%–4.6%) and N-terminal pro-brain natriuretic peptide plasma levels of 1,434 ng/L (1035–2149 ng/L). The median follow-up period was 5.6 years (2.7–8.5 years). The reoperation-free long-term survival rate up to 10 years was 66.2%. Combined operative success and perioperative safety were achieved in 94% and 76% of patients, respectively. Additional TVR was performed in 56.7% of patients, without any significant difference in survival rates compared to the group without TVR (p = 0.417; HR 1.473, 95% CI 0.578–3.757). Conclusion Less invasive MV repair for secondary MR shows excellent operative success and safety in selected patients. Freedom from significant MR and from the need for reoperation indicates long-lasting efficacy. These results should be considered in heart team discussions regarding allocation of patients to surgical mitral procedures.